Renal function in Ethiopian HIV-positive adults on antiretroviral treatment with and without tenofovir - Yilma, Daniel (BMC Infect Dis, 2020)
BACKGROUND: Limited data are available on the effect of antiretroviral treatment (ART) or Tenofovir disoproxil fumarate (TDF) on renal function in Ethiopians. We aimed to assess factors associated with renal function changes during the first year of ART with special focus on TDF. METHODS: HIV positive persons who were ≥ 18 years of age and eligible for ART initiation were recruited. Creatinine measurement to estimate glomerular filtration rate (eGFR) and spot urine analyses were performed at baseline and after 3, 6 and 12 months of ART. Univariate and multivariate linear regression and univariate logistic regression were used to determine factors associated with eGFR as continuous and categorical variable respectively. A linear mixed model was used to assess 12 month eGFR difference in TDF and non-TDF based regimen. RESULT: Of 340 ART-naïve HIV patients with baseline renal function tests, 82.3% (279/339) were initiated on a TDF based ART regimen. All patients were on non-nucleoside reverse transcriptase inhibitors (NNRTI) based ART regimen. The median (IQR) change in eGFR with 12 months of ART was 0.8 (− 11.1; 10.0) ml/min/1.73m(2). About 41 and 26.9% of HIV patients had a drop of greater than 3 and 10 mL/min/1.73 m(2) in eGFR at 12 month, respectively. However, none of the HIV patients declined to < 60 ml/min/1.73m(2) within 12 months. Moreover, none of the HIV patients had persistent proteinuria or glycosuria. Older HIV patients especially age > 45 years and those with unsuppressed viral load at 6 month of ART had a significantly lower eGFR at 12 months of ART initiation. However, there was no difference in 12 month eGFR between HIV patients initiated on TDF based regimen and non-TDF based regimen. CONCLUSION: Renal function remained stable with no difference between HIV patients treated with TDF or non-TDF NNRTI based ART regimen over 12 months. However, older HIV patients and those with unsuppressed viral load deserve special focus on renal monitoring. Data on long-term safety of TDF (> 1 year) is still warranted in this population.